Plano de bairro e a construção democrática do espaço urbano: avaliação dos instrumentos de participação popular no Jardim Lapenna – São Paulo/SP – Brasil - Urbini, Bruna Moreiras (2021)
The accelerated and uneven growth, in which the development of large and medium-sized Brazilian cities was shaped, was not appropriately accompanied by urban planning, resulting in a state of urban crisis, which affects, in a special way, the low-income population located in peripheral areas where there is a lack of infrastructure and services. In this context, participatory projects that encourage the improvement of the quality of life of this most affected population emerge. In this context, participatory projects that encourage the improvement in the creation of the local urban space emerge, an example of the Jardim Lapenna Neighborhood Plan, developed by the Getúlio Vargas Foundation and Tide Setúbal Foundation, meaning to strengthen an active and effective community organization, encourage sustainable actions and ensure adequate infrastructure for the resident population. According to the established schedule, the established changes are expected to occur by the year 2029. However, bibliographic bases confirm that there is a lack of studies assessing the effectiveness of the aforementioned in ensuring the actual participation of the local population in the elaboration of it. In this sense, this dissertation will analyze the contributions of the Jardim Lapenna Neighborhood Plan to the democratic production of contemporary urban space. It is an exploratory and qualitative study, based on a case study and which will use bibliographic survey, document analysis, field research and interviews. It is expected that the results of the present research will allow a better understanding of the effectiveness of the referred Plan in contributing to the democratic construction of urban space, as a way of improving the methodology addressed. In addition, it is expected that the analysis to be presented will contribute to the improvement of this type of urban intervention.